DNA barcoding the phyllosoma of Scyllarides squammosus (H. Milne Edwards, 1837) (Decapoda: Achelata: Scyllaridae) - Palero, Ferran; Genis-Armero, Rebeca; Hall, Michael R.; Clark, Paul F. (Zootaxa, 2016)
Scyllarides has the largest number of species with commercial importance within the Scyllaridae family. As for other achelate lobsters, however, little is known of the unique long-lived planktonic phyllosoma stages of any of these tropical and temperate species. Recently, a large and diverse collection of Scyllaridae phyllosoma, compiled from cruises along the Coral Sea and spanning several years, has been analysed. Molecular evidence from DNA-barcoding and phylogenetic analyses is provided here on the identity of S. squammosus phyllosoma larvae, including stages that were previously undescribed or poorly known. As a consequence, the growth and morphological changes that occur during the mid- to late-stages of S. squammosus larval development is now well-documented. Furthermore, an additional collection of S. squammosus larvae, described by Alain Michel and thought to be no longer extant, were discovered in the crustacean collection of the Muséum national d'Histoire naturelle, Paris. This new molecular and morphological information is complemented by a review of the literature. As a result, descriptions of key larval characters by a number of authors were evaluated and appear to suggest the existence of distinct groups of larvae within Scyllarides. From a combination of adult and larval morphology, and molecular data, the results presented here revealed inconsistencies with regard to the affinities of species assigned to Scyllarides. This new evidence will contribute to future studies addressing the phylogenetic relationships within the genus.